Sulfonation process for efficient scale-up synthesis of janus carbon nanofluids from waste plastics
Patent Information
- Application Number
- CN202580023818.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-14
- Filing Date
- 2025-03-13
- Publication Date
- 2026-10-30
AI Technical Summary
在应对我们不断增长的能源需求时,常规化石燃料仍然是主要能源来源;然而,它们正变得越来越难以从成熟油田中开采
[0006]所要求保护的主题的其他方面和优点将从以下的描述和所附的权利要求书中变得明显。
Smart Images

Figure CN123022776A_ABST
Abstract
Description
Background Technology
[0001] Among the major challenges facing the modern world, meeting energy demands and protecting the environment rank highest. Conventional fossil fuels remain the primary energy source in addressing our ever-increasing energy needs; however, they are becoming increasingly difficult to extract from mature oil fields. Recent advances in petroleum engineering research have demonstrated that nanomaterials can be used in oil flooding technologies (often referred to as nanofluid flooding) to improve oil displacement. One advantage of nanofluids stems from the small size of the nanomaterials they contain, which can alter the wettability of reservoir rocks and / or change the interfacial tension (IFT) at the water-oil interface to enhance oil recovery. However, various constraints influence the fluid-fluid and fluid-rock interactions of current nanofluids and subsequently, oil recovery rates.
[0002] Similarly, while environmental protection is a long-term goal, plastics, as one of the most widely used materials in the modern world, are highly durable and difficult to degrade. Therefore, developing efficient strategies for recycling plastic materials has become a primary objective for various industries. Summary of the Invention
[0003] This overview is provided to introduce some options of ideas, which will be further described in the detailed description below. This overview is not intended to identify key or essential features of the claimed subject matter, nor is it intended to serve as an aid in limiting the scope of the claimed subject matter.
[0004] In one aspect, the embodiments disclosed herein relate to a method for preparing an enhanced oil recovery composition (or oil recovery composition). The method includes: carbonizing waste plastic material to provide carbon microparticles; functionalizing the carbon microparticles using an SO3-containing gas such that the carbon microparticles include a hydrophilic surface; and grinding the carbon microparticles to provide carbon nanoparticles. The carbon nanoparticles include both hydrophilic and hydrophobic surfaces.
[0005] In another aspect, the embodiments disclosed herein relate to a method for enhancing oil recovery. The method includes: introducing an enhanced oil recovery composition containing carbon microparticles having hydrophilic and hydrophobic surfaces into a hydrocarbon-bearing formation; displacing hydrocarbons from the hydrocarbon-bearing formation; and recovering the hydrocarbons.
[0006] Other aspects and advantages of the claimed subject matter will become apparent from the following description and the appended claims. Attached Figure Description
[0007] Figure 1 This is a block flowchart of a method according to one or more embodiments of the present disclosure.
[0008] Figure 2 This is a schematic diagram of carbon particles before and after grinding, according to one or more embodiments of this disclosure.
[0009] Figure 3 This is a block flowchart of a method according to one or more embodiments of the present disclosure.
[0010] Figure 4A and Figure 4B This is an image of a solvent mixture containing carbon nanoparticles according to one or more embodiments of this disclosure. Detailed Implementation
[0011] Recent advances in Enhanced Oil Recovery (EOR) technology have demonstrated the effective use of nanotechnology in EOR fluids. Typically, nanomaterials contained in EOR fluids can withstand the high temperatures and pressures of subsurface reservoir systems and exhibit different surface properties compared to organic molecules in porous media such as reservoir rocks, thus enabling access to oil that is inaccessible to surfactants and polymers used in conventional EOR methods. Additional benefits of using this technology, based on the specific physical properties and characteristics of a given nanomaterial, can include altering mineral wettability, reducing interfacial tension (IFT) at the oil-water interface, changing fluid viscosity, and / or generating structural separation pressures at the oil / rock interface. In particular, Janus nanomaterials with two or more distinct chemical or physical properties on their surface possess dual nanoparticle properties and surfactant-like properties. Therefore, developing economical and sustainable methods to produce low-cost nanomaterials for field use would be highly beneficial.
[0012] Plastics, ubiquitous in modern society, are made from a variety of synthetic polymer materials that typically degrade very slowly. Since most polymers are formed from chains primarily containing carbon atoms, they are excellent precursors for carbon materials such as, for example, carbon nanoparticles. Because EOR nanofluids can exhibit enhanced oil recovery compared to conventional fluids, carbon nanoparticles derived from waste plastic materials can be used in EOR compositions and methods. Such compositions and methods will help address two major challenges in the modern world: ever-increasing energy demands and environmental protection. Therefore, this invention relates to methods for preparing carbon nanoparticles from waste plastic materials, and EOR compositions and methods using such carbon nanoparticles.
[0013] Method for preparing Janus carbon nanoparticles
[0014] In one aspect, the embodiments disclosed herein relate to a method for preparing carbon nanoparticles for use in EOR compositions. Specifically, the carbon nanoparticles can be prepared from waste plastic materials, and therefore, this method can also be applied to methods for recycling waste plastics. The method may include: carbonizing the waste plastic material to form carbon microparticles; functionalizing the carbon microparticles; and grinding the carbon microparticles to provide Janus carbon nanoparticles with asymmetric surface properties.
[0015] The method 100 for preparing carbon nanoparticles according to this disclosure is shown in... Figure 1 In China, and with reference Figure 1 Let's discuss this further. First, in method 100, the waste plastic material is carbonized via pyrolysis process 102. As used herein, "carbonization" refers to the process in which carbon-containing materials (such as the aforementioned waste plastics) are converted or "carbonized" at high temperatures in an inert atmosphere into materials, or are converted or "carbonized" into materials primarily composed of amorphous carbon. Therefore, the waste plastic material can be any waste plastic material containing carbon (such as carbon in hydrocarbons or aromatic rings). Suitable waste plastic materials that can be carbonized include polymers such as polypropylene (PP), polystyrene (PS), acrylonitrile-butadiene-styrene (ABS), polyethylene terephthalate (PET), polyester (PES), polyamide (PA), polyvinyl chloride (PVC), polyurethane (PU), polycarbonate (PC), polyvinylidene chloride (PVDC), polyethylene (PE), and combinations thereof. In some embodiments, the waste plastic material includes PET, PP, PVC, PS, high-density polyethylene (HDPE), or low-density polyethylene (LDPE). The waste plastic material can be post-consumer waste plastic material, such as, for example, plastic water bottles.
[0016] In one or more embodiments, prior to carbonization, the waste plastic material is processed by cutting or grinding to provide plastic fragments. The waste plastic material can be processed into plastic fragments of suitable size. For example, in one or more embodiments, the plastic fragments have suitable dimensions in the millimeter to sub-millimeter size range, such as 1 × 1 × 1 mm or 0.5 × 0.5 × 5 mm, etc.
[0017] Carbonization of waste plastic materials can be carried out according to any method known in the art. In one or more embodiments, the waste plastic material is carbonized by heating to an elevated temperature for a sufficient amount of time in an inert atmosphere (such as nitrogen (N2) or argon (Ar)) or under vacuum. During pyrolysis, the elevated temperature can be in the range of 300°C to 550°C. For example, in one or more embodiments, the waste plastic material is carbonized at an elevated temperature in the range of a lower limit of one of 300°C, 325°C, 350°C, 375°C, 400°C, and 425°C to an upper limit of one of 425°C, 450°C, 475°C, 500°C, 525°C, and 550°C, wherein any lower limit can be paired with any mathematically compatible upper limit.
[0018] As described above, waste plastic materials can be heated at elevated temperatures for a sufficient amount of time to achieve carbonization. In one or more embodiments, the waste plastic materials can be heated for a duration ranging from about 10 minutes to about 60 minutes. For example, the carbonization of waste plastic materials can take a duration ranging from a lower limit of one of 10 minutes, 15 minutes, 20 minutes, 35 minutes, 30 minutes, and 35 minutes to an upper limit of one of 40 minutes, 45 minutes, 50 minutes, 55 minutes, and 60 minutes, where any lower limit can be paired with any mathematically compatible upper limit. Additionally, in one or more embodiments, the waste plastic materials are carbonized in an inert atmosphere (such as, for example, nitrogen or argon) or in a vacuum.
[0019] The carbonization of waste plastic materials can be confirmed using analytical methods known in the art. Analytical spectroscopic methods (such as Raman spectroscopy, etc.) 1 H NMR spectroscopy, 13 C NMR spectroscopy, infrared (IR) spectroscopy, etc., can be used to characterize carbonized waste plastic materials and confirm their chemical structure.
[0020] Carbonized waste plastic material can be further processed to provide powder. In one or more embodiments, the waste plastic is processed by ball milling. In such embodiments, abrasive media (e.g., Netzsch, 0.45 mm zirconium oxide, ZetaBeads® Plus 0.4) and lubricants (such as ethylene glycol, ethanol, or water) can be used in a ball mill (e.g., Netzsch Minicer). Other suitable abrasive media include, but are not limited to, zirconium oxide, tungsten carbide, silicon carbide, alumina, and steel balls. The average diameter of the abrasive media can be larger than the average diameter of the powder prepared by grinding. For example, the particles of the abrasive media can have diameters in the millimeter or sub-millimeter range. The powder can include particles with an average particle size in the micrometer range. Therefore, the powder may also be referred to herein as “carbon microparticles.” Method 100 includes further grinding the particles of the powder to provide carbon microparticles. The carbon microparticles disclosed herein can have an average particle size of about 5.0 µm to about 20 µm. The particle size can be measured by scanning electron microscopy (SEM), transmission electron microscopy (TEM), or by dynamic light scattering (DLS). For example, in one or more embodiments, the average particle size of the carbon microparticles may be in the range of a lower limit of one of 5.0 µm, 7.0 µm, 10 µm, and 12 µm to an upper limit of one of 12 µm, 15 µm, 17 µm, and 20 µm, wherein any lower limit may be paired with any mathematically compatible upper limit. In some embodiments, the carbon microparticles have an average particle size of about 10 µm.
[0021] After carbonizing the waste plastic material in method 100, the resulting carbon microparticles can be functionalized 104. Functionalization of the carbon microparticles provides hydrophilic functional groups on the particle surface. These hydrophilic surface functional groups can exhibit strong hydrogen bonding capabilities. Suitable hydrophilic surface functional groups include sulfonic acid groups. The functionalization of the carbon microparticles can be carried out using an SO3-containing gas. The functionalization process involves flowing the SO3-containing gas over the carbon microparticles, causing the SO3 to bind to the particle surface. The SO3-containing gas may also include N2 gas. The SO3 to N2 ratio can range from about 5:95 (SO3:N2) to 100% SO3. For example, in one or more embodiments, the SO3 to N2 ratio can be 5:95, 10:90, 20:80, 40:60, 50:50, 70:30, 90:10, or 100% SO3. The SO3-containing gas can be supplied at a flow rate and time sufficient to achieve the desired surface functionalization. The flow rate can range from 0.1 mL / min to 1 mL / min. During the functionalization process, the carbon particles can be stirred using a magnetic stir bar or a top-mounted mixer.
[0022] In one or more embodiments, carbon microparticles are combined with SO3-containing gas at elevated temperatures for a period of time to provide hydrophilic surface functional groups. The elevated temperatures can range from about 30°C to 70°C. For example, in one or more embodiments, the functionalization of the carbon microparticles is carried out at elevated temperatures ranging from a lower limit of one of 30°C, 40°C, and 50°C to an upper limit of one of 50°C, 60°C, and 70°C, wherein any lower limit can be paired with any mathematically compatible upper limit.
[0023] Carbon microparticles can be combined with SO3-containing gas at such elevated temperatures and maintained for a period of time to provide fully functionalized carbon microparticles. In other words, the functionalized mixture can be maintained for a period of time such that the entire surface of the resulting carbon microparticles comprises hydrophilic surface functional groups. Thus, functionalization can take from 5 minutes to 30 minutes to provide fully functionalized carbon microparticles. For example, in one or more embodiments, the carbon microparticles can be contacted with the functionalizing agent for a period of time ranging from the lower limit of one of 5 minutes, 10 minutes, 11 minutes, 12 minutes, 13 minutes, 15 minutes, and 15 minutes to the upper limit of one of 30 minutes, where any lower limit can be paired with a mathematically compatible upper limit.
[0024] During functionalization, SO3-containing gas may be released as waste gas. The waste gas may require neutralization. Neutralization of the waste gas can occur by bubbling the waste gas through an alkali. The alkali can be any strong base capable of neutralization. In one or more embodiments, the alkali is NaOH. The alkali solution can be an aqueous solution. The concentration of the aqueous solution can be from 0.1 M to 10 M. For example, in one or more embodiments, the alkali concentration of the aqueous solution can be in the range of a lower limit of one of 0.1 M, 0.5 M, 1 M, 2 M, and 5 M to an upper limit of one of 5 M, 6 M, 7 M, 8 M, 9 M, and 10 M, wherein any lower limit can be paired with a mathematically compatible upper limit.
[0025] After surface functionalization, the originally hydrophobic carbon particles can be well dispersed in water, indicating that uniform sulfonation has occurred on the carbon surface. The sulfonated carbon surface can be confirmed by FTIR spectroscopy (Nicolet iS50R FTIR spectrometer). Compared to the original carbon particles, the functionalized carbon particles show improved dispersion at 3450 cm⁻¹. -1 1625 cm -1 1385 cm -1 and 1100 cm -1 A new vibration zone appeared at that location.
[0026] Following the functionalization of the carbon microparticles, method 100 includes further grinding the functionalized microparticles to provide carbon nanoparticles 106. In one or more embodiments, a ball mill can be used to grind the carbon microparticles into nanoparticles. In such embodiments, a grinding media (e.g., Netzsch, 0.2 mm zirconium oxide, ZetaBeads® Plus 0.2) and a lubricant (e.g., ethylene glycol, ethanol, or water) can be used in a ball mill (e.g., Netzsch Minicer). Suitable grinding media include, but are not limited to, zirconium oxide, tungsten carbide, silicon carbide, alumina, and steel balls. The average diameter of the grinding media can be larger than the average diameter of the carbon microparticles. For example, the particles of the grinding media can have sub-millimeter or micrometer-scale diameters. Suitable lubricants include, but are not limited to, propylene glycol, ethylene glycol, ethanol, water, and combinations thereof. In one or more embodiments, a MiniCer ball mill supplied by Netzsch, ethylene glycol as a lubricant, and 0.2 mm zirconium oxide beads as the grinding media are used to grind the carbon microparticles into nanoparticles.
[0027] When grinding carbon microparticles using a ball mill, the microparticles can be ball-milled at a sufficient grinding speed for a suitable period of time to provide carbon nanoparticles. If the grinding speed is in the range of approximately 2000 rpm to approximately 4000 rpm, this grinding speed is likely sufficient. For example, a sufficient grinding speed can be in the range of a lower limit of one of 2000 rpm, 2200 rpm, 2400 rpm, 2600 rpm, 2800 rpm, and 3000 rpm to an upper limit of one of 3000 rpm, 3200 rpm, 3400 rpm, 3600 rpm, 3800 rpm, and 4000 rpm, where any lower limit can be paired with any mathematically compatible upper limit. To provide carbon nanoparticles, the microparticles can be ground for a period of time ranging from 1 hour to 5 hours. For example, in one or more embodiments, the milling of functionalized carbon microparticles is sustained for a period of time ranging from a lower limit of one of 1.0 hours, 1.5 hours, 2.0 hours, and 2.5 hours to an upper limit of one of 3.0 hours, 3.5 hours, 4.0 hours, 4.5 hours, and 5.0 hours, wherein any lower limit may be paired with any mathematically compatible upper limit.
[0028] As described above, milling functionalized carbon microparticles can provide carbon nanoparticles. Specifically, carbon nanoparticles are provided by breaking carbon microparticles into smaller, asymmetrically surface-functionalized nanoscale particles. Since Janus carbon nanoparticles are fragments of carbon microparticles, they can possess both a hydrophilic surface derived from the hydrophilic surface of the carbon microparticles and a hydrophobic surface derived from the core of the carbon microparticles, which is composed of amorphous carbon. This process and the resulting carbon nanoparticles are schematically depicted in… Figure 2 As shown in the image. Figure 2As shown, functionalized carbon microparticles 201 can be processed to provide Janus carbon nanoparticles 203 having a hydrophilic surface 205 and a hydrophobic surface 207. In one or more embodiments, the hydrophilic surface of the carbon nanoparticles includes the same hydrophilic functional groups as those of the carbon microparticles. On the other hand, the hydrophobic surface of the carbon nanoparticles can be primarily composed of carbon. The hydrophobic surface can be non-sulfonated. Ball milling of the functionalized carbon microparticles 201 can produce the hydrophobic surface.
[0029] In one or more embodiments, the carbon nanoparticles have an average particle size, as measured by scanning electron microscopy (SEM), in the range of about 5 nm to 500 nm. For example, the average particle size of carbon nanoparticles prepared according to the disclosed method may be in the range of a lower limit of one of 5 nm, 10 nm, 50 nm, and 100 nm to an upper limit of one of 100 nm, 200 nm, 300 nm, 400 nm, and 500 nm, wherein any lower limit may be paired with any mathematically compatible upper limit.
[0030] As described above, the Janus carbon nanoparticles according to this disclosure have both hydrophilic and hydrophobic surfaces. Therefore, the disclosed carbon nanoparticles can possess unique properties, such as surfactant-like surface properties. For example, as characterized by the Langmuir isotherm, the carbon nanoparticles of this disclosure can exhibit adsorption similar to that of conventional surfactants. Surfactants are widely used in enhanced oil recovery (EOR) due to their dual hydrophobic and hydrophilic properties. Therefore, the carbon nanoparticles of one or more embodiments may be beneficial to the EOR process when incorporated into EOR fluid compositions.
[0031] EOR nanofluid composition
[0032] In another aspect, the embodiments disclosed herein relate to compositions for enhancing oil recovery. EOR nanofluids may include nanomaterials and water-based fluids.
[0033] In one or more embodiments, the EOR nanofluid comprises carbon nanoparticles. The carbon nanoparticles can be prepared according to the methods described above. Therefore, Janus carbon nanoparticles are as previously described.
[0034] EOR nanofluids may include Janus carbon nanoparticles in an amount ranging from about 0.01 wt% to about 3.0 wt%. For example, in one or more embodiments, Janus carbon nanoparticles are present in the EOR nanofluid in an amount ranging from a lower limit of one of 0.01 wt%, 0.05 wt%, 0.1 wt%, 0.5 wt%, and 1.0 wt% to an upper limit of one of 1.0 wt%, 1.5 wt%, 2.0 wt%, 2.5 wt%, and 3.0 wt%, wherein any lower limit may be paired with any mathematically compatible upper limit.
[0035] In one or more embodiments, the EOR nanofluid comprises a water-based fluid. The water-based fluid includes water. Water can be distilled water, deionized water, tap water, fresh water from surface or groundwater sources, produced water, formation water, natural and synthetic brine, brackish water, natural and synthetic seawater, black water, brown water, grey water, blue water, drinking water, non-drinking water, other water, and combinations thereof suitable for use in a wellbore environment. In one or more embodiments, the water used may naturally contain contaminants such as salts, ions, minerals, organic matter, and combinations thereof, provided that these contaminants do not interfere with the operation of the drilling fluid.
[0036] In one or more embodiments, the EOR nanofluid comprises water in the range of about 97% to 99.9% by weight, based on the total weight of the EOR fluid.
[0037] In one or more embodiments, the water used in the EOR composition may have elevated salt or ion levels compared to fresh water, such as salts or ions naturally present in formation water, produced water, seawater, and brine. Increasing the saturation of water by increasing the concentration of salts or other organic compounds in the water can increase the density of the water, and thus increase the density of the EOR fluid. Suitable salts may include, but are not limited to, alkali metal halides, such as chlorides, hydroxides, or carboxylates. In one or more embodiments, the salts included as part of the water-based fluid may include salts of sodium, calcium, cesium, zinc, aluminum, magnesium, potassium, strontium, silicon, lithium, chlorides, bromides, carbonates, iodides, chlorates, bromates, formates, nitrates, sulfates, phosphates, oxides, and fluorides, and combinations thereof.
[0038] In one or more embodiments, the EOR fluid comprises one or more salts in amounts ranging from about 0 ppm to about 225,000 ppm (parts per million) based on TDS (total dissolved solids). For example, the EOR fluid may contain one or more salts in amounts ranging from the lower limit of any one of 0 ppm, 5,000 ppm, 10,000 ppm, 20,000 ppm, 30,000 ppm, 50,000 ppm, 75,000 ppm, 100,000 ppm, and 125,000 ppm to the upper limit of any one of 125,000 ppm, 150,000 ppm, 175,000 ppm, 200,000 ppm, and 225,000 ppm, wherein any lower limit may be used in combination with any mathematically compatible upper limit.
[0039] In one or more embodiments, the EOR fluid includes one or more additives. Any additives known in the art for EOR nanofluids can be used. Examples of such additives include, but are not limited to, surfactants, stabilizers, and / or mixtures thereof. In one or more embodiments, the additives may be included in the EOR fluid in an amount ranging from 0 to about 3% by weight.
[0040] In one or more embodiments, the EOR nanofluid can be characterized based on several properties, such as viscosity, density, and uniformity. Furthermore, the presence of carbon nanoparticles in the fluid can lead to a reduction in the interfacial tension between the EOR fluid and the oil within the reservoir.
[0041] Method of EOR
[0042] In another aspect, embodiments of this disclosure relate to a method for enhancing oil recovery using the aforementioned enhanced oil recovery fluid composition. This method may include: introducing the enhanced oil recovery fluid into a hydrocarbon-bearing formation; displacing hydrocarbons from the hydrocarbon-bearing formation; and recovering the hydrocarbons.
[0043] Method 300 according to this disclosure is shown in Figure 3 In China, and with reference Figure 3 Let's discuss this further. First, in method 300, an enhanced oil recovery (EOR) fluid is introduced into a hydrocarbon-bearing formation 302. The EOR nanofluid is as previously described. The hydrocarbon-bearing formation may include petroleum. In one or more embodiments, the hydrocarbon-bearing reservoir has had approximately one-third of its hydrocarbon content extracted. The EOR nanofluid can be introduced into the hydrocarbon-bearing formation using pipes and tubing known in the art. For example, a chemical injection skid can be used to introduce the EOR nanofluid into the hydrocarbon-bearing formation.
[0044] Then, in method 300, hydrocarbons are displaced from the hydrocarbon-bearing formation 304. The disclosed EOR nanofluid can be used to displace the hydrocarbons. In one or more embodiments, Janus carbon nanoparticles in the EOR nanofluid can have surfactant-like surface properties. Therefore, the disclosed Janus carbon nanoparticles can be located at the downhole oil-water interface or rock-fluid interface, and thus can improve hydrocarbon mobility or change the wettability of reservoir rocks, resulting in increased hydrocarbon displacement.
[0045] Finally, in method 300, hydrocarbons 306 can be recovered. As described above, in the presence of the disclosed EOR nanofluid, hydrocarbons can have increased fluidity and therefore increased hydrocarbon recovery from the formation. Method 300 can lead to greater recovery of the original oil initially in place (OIIP).
[0046] The embodiments of this disclosure can provide at least one of the following advantages. Current sulfonation methods known in the art often use acid treatment for functionalization. The acid can be H₂SO₄ or HNO₃. Methods using acids often generate excessive liquid waste. Furthermore, methods using acids often require a filtration process to separate the functionalized material from the acid. In contrast, the method described herein using SO₃-containing gas does not generate any liquid waste. Moreover, the method using SO₃-containing gas does not require any filtration process after functionalization.
[0047] Example
[0048] Waste plastic water bottles (polymer PET) were cut into millimeter-sized pieces, and 5 grams of plastic fragments were placed in a crucible. After heating at 450°C for 30 minutes under a nitrogen atmosphere, the resulting carbon black powder was collected. By grinding in an agate mortar, the carbon powder was easily broken into micrometer-sized particles.
[0049] The carbon structure was confirmed by Raman spectroscopy, exhibiting a structure at approximately 1365 cm⁻¹. -1 The characteristic D band at approximately 1605 cm -1 The characteristic G band at the location is shown in Figure 4, “C-MP”. The spectrum was recorded at an excitation wavelength of 532 nm using a Horiba-Revolution Raman spectrophotometer.
[0050] Two grams of carbon microparticles were placed in a flask, and the temperature was maintained at 50°C. SO3 and N2 gas were then introduced into the flask at a rate of 0.1 mL / min (50 / 50 ratio of each gas), while the carbon microparticles were mixed using an external overhead mixer. The exhaust gases were neutralized by bubbling NaOH aqueous solution into an alkaline bath. The reaction was then allowed to continue for 15 minutes, during which time the carbon microparticles were washed, filtered, and dried.
[0051] Carbon microparticles were ground using a laboratory ball mill (Netzsch, MiniCer). First, 140 mL of zirconia beads (0.45 mm in diameter) were loaded into the grinding chamber as grinding media. Then, 10 g of functionalized carbon microparticles were mixed with 200 mL of water in an open mixing container and pumped through the grinding chamber. The grinding speed was set to 3000 rpm, and the feed fluid was circulated in the grinding chamber at a flow rate of 100 mL / min. After grinding for 2 hours, the fluid was collected, the resulting carbon nanoparticles were separated by centrifugation, and washed with ethanol.
[0052] The synthesized Janus carbon nanoparticles were dispersed in a mixture of water 401 and organic solvent 403. Organic solvent 403... Figure 4A The middle is hexanol, in Figure 4B The middle component is chloroform. After phase separation, Figure 4A andFigure 4B This indicates that carbon nanoparticles 405 self-assemble at the interface between water 401 and organic solvent 403, suggesting that they possess dual surface properties (i.e., hydrophobic and hydrophilic).
[0053] Although only a few exemplary embodiments have been described in detail above, those skilled in the art will readily understand that many modifications can be made to the exemplary embodiments without substantially departing from the invention. Therefore, all such modifications are intended to be included within the scope of this disclosure as defined in the following claims.
Claims
1. A method for preparing an enhanced oil recovery composition, comprising: Carbonize waste plastic materials to provide carbon microparticles; The carbon microparticles are functionalized using SO3-containing gas, such that the carbon microparticles include a hydrophilic surface; and The carbon microparticles are ground to provide carbon nanoparticles, wherein the carbon nanoparticles include hydrophilic and hydrophobic surfaces.
2. The method according to claim 1, wherein, The carbonization of the waste plastic material further includes grinding to provide carbon microparticles.
3. The method according to claim 1 or 2, further comprising mixing the carbon nanoparticles with a water-based fluid to provide an enhanced oil recovery fluid.
4. The method according to any one of claims 1 to 3, wherein, The waste plastic materials include polymers selected from the group consisting of polypropylene (PP), polystyrene (PS), acrylonitrile-butadiene-styrene (ABS), polyethylene terephthalate (PET), polyester (PES), polyamide (PA), polyvinyl chloride (PVC), polyurethane (PU), polycarbonate (PC), polyvinylidene chloride (PVDC), polyethylene (PE), and combinations thereof.
5. The method according to any one of claims 1 to 4, wherein, The waste plastic material is waste plastic bottles.
6. The method according to any one of claims 1 to 5, wherein, Carbonizing the waste plastic material involves heating the waste plastic material at a temperature ranging from 300°C to 550°C.
7. The method according to any one of claims 1 to 6, wherein, The carbon microparticles have an average particle size in the range of 5 µm to 20 µm.
8. The method according to any one of claims 1 to 7, wherein, Functionalizing the carbon microparticles using the SO3-containing gas includes heating the carbon microparticles at a temperature of 50°C and a flow rate of 0.1 mL / min.
9. The method according to claim 8, wherein, Functionalizing the carbon particles using the SO3-containing gas further includes heating for 15 minutes.
10. The method according to any one of claims 1 to 9, wherein, The hydrophilic surface functional group is a sulfonic acid group.
11. The method according to any one of claims 1 to 10, wherein, Grinding the carbon microparticles includes ball milling the carbon microparticles at a speed of 2000 rpm to 4000 rpm for a period of 0.5 hours to 8 hours.
12. The method according to any one of claims 1 to 11, wherein, The carbon nanoparticles have an average particle size in the range of 5 nm to 500 nm.
13. The method according to any one of claims 1 to 12, wherein, The hydrophobic surface is a non-sulfonated carbon surface.
14. The method according to any one of claims 11 to 13, wherein, The hydrophobic surface is produced by ball milling.
15. The method according to any one of claims 3 to 14, wherein, The water-based fluid is water, seawater, or salt water.
16. The method according to any one of claims 3 to 15, wherein, The water-based fluid includes one or more additives selected from the group consisting of surfactants, stabilizers, and combinations thereof.
17. A method for enhancing oil recovery, comprising: The enhanced oil recovery composition according to claim 3 is introduced into a hydrocarbon-bearing formation; Displace hydrocarbons from the hydrocarbon-bearing strata; as well as Harvest the aforementioned hydrocarbons.
18. The method according to claim 17, wherein, The carbon nanoparticles are present in an amount ranging from 0.01 wt% to 3.0 wt%.
